2015
DOI: 10.1212/nxi.0000000000000161
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia T1 hyperintensity in LGI1-autoantibody faciobrachial dystonic seizures

Abstract: Objective:To characterize the clinical features and MRI abnormalities of leucine-rich glioma-inactivated 1 (LGI1)-autoantibody (Ab) faciobrachial dystonic seizures (FBDS).Methods:Forty-eight patients with LGI1-Ab encephalopathy were retrospectively identified by searching our clinical and serologic database from January 1, 2002, to June 1, 2015. Of these, 26 met inclusion criteria for this case series: LGI1-Ab seropositivity and FBDS. In a separate analysis of all 48 patients initially identified, the MRIs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
149
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 173 publications
(168 citation statements)
references
References 25 publications
12
149
6
1
Order By: Relevance
“…We did not find extratemporal lesions, i.e. basal ganglia hyperintensities in our patients including FBDS cases in contrast to earlier studies [9,10,14,30,31]. Nevertheless, we found that higher volume of the putamen was associated with better cognition measured by ACE test at 23.4±7.6 months indicating the affection of the basal ganglia also in our studies, and that basal ganglia atrophy may affect functional outcomes in patients with LGI1 encephalitis.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We did not find extratemporal lesions, i.e. basal ganglia hyperintensities in our patients including FBDS cases in contrast to earlier studies [9,10,14,30,31]. Nevertheless, we found that higher volume of the putamen was associated with better cognition measured by ACE test at 23.4±7.6 months indicating the affection of the basal ganglia also in our studies, and that basal ganglia atrophy may affect functional outcomes in patients with LGI1 encephalitis.…”
Section: Discussioncontrasting
confidence: 99%
“…For such correlation, we used (i) midline structures with significant group differences (brainstem, combined volume of the mid-posterior and central parts of the corpus callosum); (ii) the bilateral volumes of those structures where significant difference were shown between patients and controls for both sides (cerebral white matter, cerebellar gray matter); (iii) and the bilateral volumes of lateral ventricles (a general marker of global atrophy) along with putamen and caudate, i.e. areas that have been shown to be highly affected by the disease [7][8][9][10].…”
Section: Volumetric Changes 331±18 Months After Disease Onsetmentioning
confidence: 99%
See 2 more Smart Citations
“…Imaging analyses during this early disease stage revealed alterations of basal ganglia metabolism using FDG-PET6 11 and transient T1 and T2 basal ganglia hyperintensities contralateral to the side of FBDS 6. Another recent study linked hypermetabolism of the primary motor cortex and frontal cortex EEG changes to contralateral FBDS 5…”
Section: Introductionmentioning
confidence: 94%